2005
DOI: 10.1111/j.0887-378x.2005.00337.x
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacy Utilization and the Medicare Modernization Act

Abstract: To control expenditures and use medications appropriately, the Medicare drug coverage program has established pharmacy utilization management (PUM) measures. This article assesses the effects of these strategies on the care of seniors. The literature suggests that although caps on drug benefits lower pharmaceutical costs, they may also increase the use of other health care services and hurt health outcomes. Our review raises concerns regarding the potential unintended effects of the Medicare drug program's PUM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
42
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(42 citation statements)
references
References 51 publications
0
42
0
Order By: Relevance
“…In the US, 97% of people over 65 years who receive incomplete Medicare coverage need supplemental insurance (Roberts 2006). Since the Medicare Prescription Drug Improvement and Modernization Act of 2003 only went into effect in 2006, its impact on suboptimal medication use is still to be determined (Maio et al 2005). …”
Section: Pharmacoeconomicsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the US, 97% of people over 65 years who receive incomplete Medicare coverage need supplemental insurance (Roberts 2006). Since the Medicare Prescription Drug Improvement and Modernization Act of 2003 only went into effect in 2006, its impact on suboptimal medication use is still to be determined (Maio et al 2005). …”
Section: Pharmacoeconomicsmentioning
confidence: 99%
“…Although underuse can result in morbidity and health care cost, the cost of the medication is believed to be one of the most important determinants of underuse (Hanlon et al 2001; Stuart 2004; Maio et al 2005). Tiotropium has demonstrated the highest expected net benefit for ratios of the willingness to pay per quality-adjusted life-year (QALY) (Rutten-van Mölken et al 2007).…”
Section: Pharmacoeconomicsmentioning
confidence: 99%
“…The substantial body of literature on prescription drug charges already includes several reviews. However, the remit of most of these reviews is constrained by a focus on, for example, specific populations [2-4]; a sub-set of the literature such as studies from the United States, the United Kingdom, and/or Canada [5-9]; specific forms of prescription drug charges such as reference pricing [10,11] and tiered formularies [12]; or the main articles in the area [7,13-16]. We add to existing reviews by covering studies carried out in a wider range of high-income countries and reviewing papers published in languages other than English.…”
Section: Introductionmentioning
confidence: 99%
“…The study concluded that individuals with larger coinsurance rates spent less money on prescription drugs, primarily because they filled fewer prescriptions, as opposed to purchasing more low-cost generic medications (Leibowitz, Manning, and Newhouse 1985). Subsequent analyses using observational data confirmed the negative relationship between cost sharing and drug spending across various groups, including the Medicaid population (Reeder and Nelson 1985;Soumerai et al 1987), Medicare population (Eaddy et al 2012;Maio et al 2005), and the privately insured (Druss et al 2004;Eaddy et al 2012;Huskamp et al 2003;Joyce et al 2002;Mager and Cox 2007). Recent estimates of the price elasticity of demand for prescription drugs from observational studies that account for patient selection into insurance range from 0.1 to 0.6 depending on type of drug (Contoyannis et al 2005;Meyerhoefer and Zuvekas 2010).…”
Section: Background and Literature Reviewmentioning
confidence: 94%